The TIMI Risk Index as a Predictor of Contrast-Induced Nephropathy in Patients Undergoing Primary Percutaneous Coronary Intervention at Haji Adam Malik Hospital Medan - Purba, Antonius Leonardo; Hasan, Refli; Raynaldo, Abdul Halim (Journal of Society Medicine, 2025)
Introduction: ST-segment elevation myocardial infarction (STEMI) is a severe cardiovascular condition requiring urgent treatment through Primary Percutaneous Coronary Intervention (PPCI). However, PPCI increases the risk of Contrast-Induced Nephropathy (CIN), a condition characterized by a significant rise in serum creatinine levels. To minimize the risk of CIN, identifying patients at high risk is essential. This study evaluates the TIMI Risk Index (TRI) as a predictor of CIN in STEMI patients undergoing PPCI at Haji Adam Malik Hospital, Medan. Methods: This observational analytical study employed a cross-sectional design, focusing on STEMI patients with symptoms lasting less than 12 hours who underwent PPCI between January 2023 and December 2024. Participants were selected according to inclusion and exclusion criteria. Bivariate analysis was used, with the chi-square test for normally distributed data and the Fisher exact test for non-normally distributed data, with a significance level of p < 0.05. Results: The results indicated that TRI effectively predicted CIN occurrence, with a p-value of 0.0001, an area under the curve (AUC) of 0.834, and a 95% confidence interval (CI) of 0.752–0.916. A TRI cut-off score of 23.47 demonstrated a sensitivity of 77.3%, specificity of 77%, a positive predictive value (PPV) of 47.05%, and a negative predictive value (NPV) of 91.8%. Conclusion: In conclusion, the TRI with a cut-off score of 23.47 is a reliable tool for predicting CIN in STEMI patients undergoing PPCI, offering high sensitivity, specificity, and NPV, which can help improve clinical outcomes by identifying at-risk patients.